2016
DOI: 10.1097/mjt.0000000000000363
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Circadian Rhythm Disruption and Alcohol on the Oxidative Stress Level in Rat Brain

Abstract: Alcohol abuse is often associated with disrupted circadian rhythms and sleep, and the link seems to be bidirectional. In addition, it has been shown that exposure to constant illumination may increase lipid peroxidation in tissues. In this study, we investigated the effects of circadian rhythm disruption (CRD) and chronic alcohol intake (A) alone and in combination (CRD+A), on the oxidative stress in total rat brain homogenate. Our results demonstrated that lipid peroxidation was increased in the brain samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…One more way is for example the free radical scavenging ability of melatonin . As jet lag raises the oxidative stress in cells, melatonin might have preserved the functional capacity of the hippocampal pyramidal neurons in our experiment due to its potent role as a protector of cells from oxidative stress.…”
Section: Discussionmentioning
confidence: 80%
“…One more way is for example the free radical scavenging ability of melatonin . As jet lag raises the oxidative stress in cells, melatonin might have preserved the functional capacity of the hippocampal pyramidal neurons in our experiment due to its potent role as a protector of cells from oxidative stress.…”
Section: Discussionmentioning
confidence: 80%
“…Metabolic reactions produce redox potential that plays an important role in circadian rhythm functioning. Previous studies have suggested that ethanol exposure (both acute and chronic) alters several aspects of the circadian rhythm 36 - 39 .…”
Section: Correlation Between Alcohol Metabolism and Histone Modificatmentioning
confidence: 99%
“…Secondary plant components, such as antioxidants [ 5 ], protect the cells and connective tissue against the development of oxidative stress, which is related to several pathological consequences, e.g., neurological [ 6 ], cardio-vascular [ 7 ], dermatological diseases [ 8 ] or aging [ 9 ]. Oxidative stress is induced by various factors, inter alia, solar radiation, smoking, alcohol consumption, lack of sleep, intensive physical activities and psychological stress [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], and therefore cannot be avoided in daily life. Oxidative stress is characterized by the generation of large amounts of reactive oxygen species (ROS), whose action is responsible for the development of premature skin aging and photo aging [ 7 , 21 ].…”
Section: Introductionmentioning
confidence: 99%